2011
DOI: 10.1177/1040638711407893
|View full text |Cite
|
Sign up to set email alerts
|

Clostridium difficile in retail meat and processing plants in Texas

Abstract: Abstract. The incidence and severity of disease associated with toxigenic Clostridium difficile have increased in hospitals in North America from the emergence of newer, more virulent strains. Toxigenic C. difficile has been isolated from food animals and retail meat with potential implications of transfer to human beings. The objective of the present study was to determine the prevalence of C. difficile in pork from sausage manufacturing plants and retail meat in Texas. Twenty-three C. difficile isolates were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
34
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 24 publications
6
34
1
Order By: Relevance
“…Analogous to our results, a study carried out in Texas by Harvey et al (9) reported resistance against clindamycin; and 100% sensitivity against vancomycin and metronidazole in positive isolates obtained from meat products.…”
Section: Discussionsupporting
confidence: 71%
“…Analogous to our results, a study carried out in Texas by Harvey et al (9) reported resistance against clindamycin; and 100% sensitivity against vancomycin and metronidazole in positive isolates obtained from meat products.…”
Section: Discussionsupporting
confidence: 71%
“…The authors suggested that this environmental contamination might be due to biofilm formation which could facilitate the attachment of spores (Esfandiari et al 2014b). In contrast, in a further study conducted in three sausage-manufacturing plants, sponge swabs collected from equipment and facilities yielded no C. difficile isolates (Harvey et al 2011b), while meat samples tested positive for the bacterium, indicating meat contamination with C. difficile from the intestinal contents of food animals.…”
Section: Routes Of Food Contaminationmentioning
confidence: 88%
“…A further study reported a prevalence of 2.2 % and 2.5 % in antimicrobial-free pigs at post-evisceration and post-chill respectively (Susick et al 2012). Harvey et al (2011b) detected 3 positive samples from a total of 10 sponge swabs collected from carcass hide, post-excision hides and ears from pigs in a processing plant in Texas. In Belgium, the prevalence reported in carcasses from slaughter pigs was 7 % (7/100) .…”
Section: Routes Of Food Contaminationmentioning
confidence: 99%
“…Finally, C difficile has been isolated from retail meats in some studies, and some have speculated food as a source of C difficile in the community. [23][24][25] In our study, NAP7 and NAP8, the strains that have been most frequently isolated from meat samples, were uncommon.…”
Section: Figurementioning
confidence: 99%